2013
DOI: 10.1590/s0044-59672013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species in Pagamea coriacea sensu lato (Rubiaceae): evidence from morphology, ecology and reproductive behavior in a sympatric context

Abstract: In this study we explore morphological and ecological variation in sympatric populations of Pagamea coriacea s.l. -a species complex from white-sand vegetation in the Amazon. A total of 147 trees were sampled and monitored at three nearby sites in Central Amazon, Brazil. Multivariate analyses of morphology indicated two distinct groups (A and B), which also differed in bark type, each containing subgroups associated with sexual dimorphism. However, a single hermaphroditic individual was observed within group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…). Similarly, a study on reproductive biology, phenotypic differences, and ecological preferences within the Pagamea coriacea complex (Rubiaceae) identified two sympatric species exploiting different gradient combinations of light and drainage within white‐sand forests (de Esteves & Vicentini ). Elucidating the number of cryptic undescribed species, and potentially incipient species undergoing ecological adaptation into white‐sands forests, will remain uncertain without more taxonomic, field, and molecular‐based studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Similarly, a study on reproductive biology, phenotypic differences, and ecological preferences within the Pagamea coriacea complex (Rubiaceae) identified two sympatric species exploiting different gradient combinations of light and drainage within white‐sand forests (de Esteves & Vicentini ). Elucidating the number of cryptic undescribed species, and potentially incipient species undergoing ecological adaptation into white‐sands forests, will remain uncertain without more taxonomic, field, and molecular‐based studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, based upon detailed molecular and morphological studies, populations confined to white-sand habitats and previously assigned to Protium subserratum (Burseraceae) were found to be distinct from populations of that occurred on non-white sand soils, and it was suggested that they should be recognized at species level (Daly & Fine 2011, Fine et al 2013. Similarly, a study on reproductive biology, phenotypic differences, and ecological preferences within the Pagamea coriacea complex (Rubiaceae) identified two sympatric species exploiting different gradient combinations of light and drainage Table S1. within white-sand forests (de Esteves & Vicentini 2013). Elucidating the number of cryptic undescribed species, and potentially incipient species undergoing ecological adaptation into whitesands forests, will remain uncertain without more taxonomic, field, and molecular-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the fine taxonomic level, closely-related species, which are often identified only by DNA barcoding (i.e., cryptic species) (Hebert et al 2004), offer valuable test cases to assess how species traits (e.g., ecological optima, behavior) contribute to speciation mechanisms. The taxonomic validity of cryptic species can be further assessed by comparing phylogenetic and ecological data, such as shown for Amazonian trees (Esteves and Vicentini 2013), bats (Santos et al 2014) and salamanders (Rissler and Apodaca 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular assessment of protist diversity may shed new light on their community ecology. With these tools, it is now possible to assess not only the fine-scale distribution patterns at the relevant taxonomic resolution but also to explore the mechanisms driving speciation as hitherto done only for macroscopic organisms (Rissler and Apodaca 2007, Esteves and Vicentini 2013, Santos et al 2014, Janzen et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Situated along the transition between the erosion‐resistant Precambrian Guyana shield and lowland Amazonia, the region is characterized by rocky outcrops and grottoes scattered throughout the rainforest (de Granville, 1988). The reserve is dominated by upland terra firme forest (Veloso et al, 1991), which grades into isolated patches of Amazonian white‐sand forests ( campinarana ; Esteves and Vicentini, 2013). Mean annual temperature at the study site ranges from 19°C to 39°C (mean = 26°C), and annual rainfall ranges from 1900 to 3500 mm, with a distinct dry season from July to November.…”
Section: Methodsmentioning
confidence: 99%